Oriental Networks : Culture, Commerce, and Communication in the Long Eighteenth Century - Clingham, Greg; Czennia, Bärbel, 1961- (Book collections on Project MUSE., 2021)
"Oriental Networks explores forms of interconnectedness between Western and Eastern hemispheres during the long eighteenth century, a period of improving transportation technology, expansion of intercultural contacts, and the emergence of a global economy. In eight case studies and a substantial introduction, the volume examines relationships between individuals and institutions, precursors to modern networks that engaged in forms of intercultural exchange. Addressing the exchange of cultural commodities (plants, animals, and artifacts), cultural practices and ideas, the roles of ambassadors and interlopers, and the literary and artistic representation of networks, networkers, and networking, contributors discuss the effects on people previously separated by vast geographical and cultural distance. Rather than idealizing networks as inherently superior to other forms of organization, Oriental Networks also considers Enlightenment expressions of resistance to networking that inform modern skepticism toward the concept of the global network and its politics. In doing so the volume contributes to the increasingly global understanding of culture and communication. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press"--